Early success and relative age effects in youth athletics: Practical implications - Kearney, P.; Brazo-Sayavera, J.; Boccia, G.; Hayes, P. (New Studies in Athletics, 2017)
To ensure a positive youth sport experience for all athletes, it is imperative that coaches, parents and administrators possess an in-depth understanding of athlete development. In this article the authors provide a review of recent research examining the relationship between success at youth and adult levels in athletics. They focus on the growing evidence that youth success is strongly influenced by an athlete's age relative to his or her peers: the relative age effect. Subsequently, they describe and evaluate a range of initiatives that have been proposed to enhance the youth sport experience in relation to relative age effects. They provide examples that federations and administrators can use to reflect on the broader consequences of their competition structures, and on the use of publically-accessible national rankings. They also provide examples to help clubs and development officers to reflect upon the methods used to educate all stakeholders, including coaches, parents and the athletes themselves, on the reality of athlete development.